Strategic Enhancement of Financial Inclusion through Shariah-Compliant Fintech: A SWOT Analysis of Bank Syariah Indonesia KCP Gunung Tua - Risma Haryani Siregar; Muhammad Syahbudi; Muhammad Ikhsan Harahap (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This research aims to determine the strategy for increasing inclusive finance through Shariah fintech at Bank Syariah Indonesia KCP Gunung Tua using SWOT analysis. A qualitative research approach was utilized. The results of the SWOT analysis revealed that the IFAS matrix scored 0.6 and the EFAS matrix scored 0.54, indicating Quadrant I and suggesting an aggressive strategy that supports growth policies by leveraging all strengths to maximize opportunities. Based on these results, the improvement strategy for BSI KCP Gunung Tua includes: first, utilizing transaction services available anytime and anywhere to attract individuals who prefer mobile banking (BSI Mobile) (S3, O3); second, capitalizing on the predominantly Muslim community in Gunung Tua, which has great potential, by offering low operational cost services from the Indonesian Shariah bank (S1, O1); third, leveraging the preference for mobile banking transactions with an easy process at BSI (S2, O3)